Effects of different concentrations of artemisinin and artemisinin-iron combination treatment on Madin Darby Canine Kidney (MDCK) cells - Shahbazfar, Amir Ali (Slovak Toxicology Society SETOX, 2012)
Artemisinin is a sesquitrepenelactone with an endoperoxide bridge. It is a naturally occurring substance from Artemisia species plants. Artemisia species have been used in oriental medicine for centuries to treat malaria, gastrointestinal helminthosia, diarrhea, and as an antipyretic and sedative agent. Antileishmanial activity of the plants has been announced a few years ago. Dogs are the most important reservoir of leishmaniasis in some parts of the world. To use it as an antileishmanial drug in dogs, its side effects on different organs, among them the kidney as the organ of elimination have to be elucidated. Artemisinin with different concentrations (0.15, 0.3, 0.6 and 1.2 μg/ml) was added to the culture of MDCK (Madin darby canine kidney) cells with and without iron (86 μg/dl). All the changes were controlled and photographed every 12 hours using an invert microscope. After 60 hours, supernatants and cell extracts were examined for LDH (lactate dehydrogenase) concentration and total protein. Also TBARS (thiobarbituric acid reactive substances) test was performed on cell extracts. Some microscopic slides were prepared from the cells and stained with hematoxylin-eosin for microscopic exams. Biochemical parameters showed cellular reaction and injury in a concentration dependent manner. Cell injury was more severe in the iron-added groups. Microscopic exams showed cell and nuclear swelling, granular degeneration, vacuole and vesicle formation, cellular detachment, piknosis, karyorrhexis, cellular necrosis and inhibition of new mitosis. On using the drug for leishmaniasis treatment in the dog, it should be done with caution and supervision.